2022
DOI: 10.3390/catal12090939
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic H2O2 Generation Using Au-Ag Bimetallic Alloy Nanoparticles loaded on ZnO

Abstract: Hydrogen peroxide (H2O2) is an important chemical as it is an environmentally friendly oxidant for organic synthesis and environmental remediation as well as a promising candidate for the liquid fuel. Photocatalytic generation of H2O2 is sustainable, and many efforts have been put into the development of new catalysts to gain high H2O2 yields. In this investigation, Au/ZnO, Ag/ZnO and Au-Ag/ZnO catalysts were prepared by the simultaneous impregnation of HAuCl4 and AgNO3 and they were used to generate H2O2 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…ZnO had a uniform nanorod shape, while the surface of Ag-ZnO contained some small nanoparticles loading onto the nanorods of ZnO. The result from SEM analysis confirmed that the silver nanoparticles were loaded over ZnO [13,21,25].…”
Section: Photocatalysts Propertiesmentioning
confidence: 74%
See 1 more Smart Citation
“…ZnO had a uniform nanorod shape, while the surface of Ag-ZnO contained some small nanoparticles loading onto the nanorods of ZnO. The result from SEM analysis confirmed that the silver nanoparticles were loaded over ZnO [13,21,25].…”
Section: Photocatalysts Propertiesmentioning
confidence: 74%
“…Silver is one of the cheapest, most stable, and non-toxic of the noble metals; with surface plasmon resonance it also can support enhancing light adsorption as well. The doped Ag onto ZnO was determined to improve the photocatalytic decomposition of methylene blue [13,15,25].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the catalyst with higher activity and selectivity for 2e – -ORR in addition to lower activity for H 2 O 2 decomposition than Au NP is the central subject. An effective means to improve the catalytic performance is alloying Au with other metals such as Ag , and Pd . Also, antimony-doped tin oxide is a very promising nonprecious MO due to the high activity for 2e – -ORR, low affinity for H 2 O 2 , extreme robustness, and the applicability to the electrochemical production of H 2 O 2 …”
Section: Summary and Future Subjectsmentioning
confidence: 99%
“…18 In addition, Ag NPs show interesting 2e − O 2 reduction behavior and oxygen adsorption properties. 26–29…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, Ag NPs show interesting 2e − O 2 reduction behavior and oxygen adsorption properties. [26][27][28][29] There is no previous report on the photocatalytic H 2 O 2 formation properties of the magnetically recyclable Ag/ CuWO 4 /NiFe 2 O 4 composite. Furthermore, the H 2 O 2 produced is used for in situ Fenton-like degradation of tetracycline.…”
Section: Introductionmentioning
confidence: 99%